Penerapan Rancangan Acak Lengkap dalam Penilaian Cara Mengajar (Studi Kasus: Jurusan Matematika FMIPA Unimed) - Dewi Lowisa Br Purba; Indah Febriani Sagala; Nagita Adella; Reski Augustian. S; Sudianto Manullang; Putri Maulidina Fadilah (Interdisciplinary Explorations in Research Journal, 2024)
This research aims to evaluate the effectiveness of lecturers' teaching methods in the Mathematics Department, FMIPA, Medan State University (Unimed) using a Completely Randomized Design (RAL) approach. This method allows controlled testing of variability between groups of students, with a sample of 60 students selected at simple random. Data was collected through a questionnaire that measured student perceptions of teaching methods, followed by analysis using ANOVA. The research results show that the teaching methods applied have a significant influence on student learning outcomes, with differences between groups detected through statistical tests. This research provides recommendations for adopting more effective teaching methods in improving the quality of education in the academic environment.